Comparative study of the cathodic cleavage of N-tosyl- and N-nosyl-protected amino acids - Zanoni, Maria Valnice Boldrin [UNESP]; Sartorello, Carlos Humberto M. [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier B.V., 1993)
The electrochemical behaviour of alanine and phenylalanine protected by the toluenesulphonyl (tosyl) and nitrobenzesulphonyl (nosyl) groups was examined in dimethyl formamide. The N-tosyl-protected amino acids are reduced in one cathodic step (-2.4 V/SCE) leading to cleavage of the SN bond after a two-electron transfer process. The N-nosyl-protected amino acids are reduced in three cathodic steps. Cyclic voltammetry and controlled potential electrolysis of N-nosyl amino acids have been used to probe the mechanism of these reductions in an aprotic medium and lead to cleavage of the SN bond in good yields ( > 60%) at -1.10 V/SCE. The comparative study of these compounds is used to comment on the applicability of the electrochemical method of removing protecting groups from amino acids. © 1993.